JUMPA Vol.4 No.2, Juni 2017 EVALUASI PROGRAM PEMBIAYAAN MIKRO DI BRI SYARIAH CABANG SERPONG: EVALUASI PROGRAM PEMBIAYAAN MIKRO DI BRI SYARIAH CABANG SERPONG - Maharani Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta (Jurnal Manajemen dan Perbankan (JUMPA), 2017)
Micro Financing Program Evaluation in Sharia BRI Branch Serpong.Implementation of the program of micro financing in BRI Syariah analysis method AHP seen against the backdrop of the debtor, business conditions, risk guarantees, financial analysis, risk analysis of the value of the ratio between the value of the priority criteria and priority value per criteria of prospective customers and clients that have been evaluated with 5 stars the criteria are then eligible to receive funding from BRI Syariah Branch Serpong. BRI Syariah provide to customers who are considered views of five criteria to be some value given priority to microfinance as requested by the prospective customer of BRI Syariah. Results of the research show that the AHP method between criteria and sub-criteria of the financing application process by weighting (Weighted Vector Sum) the Debtor of 3.693404; 1.123728 businesses; 0.405311 assurance; Finance 0.405311; 0.39008 risk then the value is divided by Consistency vector that produces a value of 6.701886 Debtor; 6.123718 businesses; 6.074523 assurance; Finance 6.074523; Risk 5.980307. It can be concluded that the criteria are more debtors affects the implementation of the financing has the highest weight is 0.551 with Inconsistency Ratio 0.027674 P, this is due to moral hazard criteria verry affect the implementation of the financing Debtor more than others. The strategy undertaken by BRI Syariah to date is by organizing several events, including seminars event market and campuses are also office buildings even held an Islamic banking. The aim of this study is to describe and analyze the implementation of micro financing in BRI Syariah is to be seen from its implementation, the strategy, the feasibility of each customer and how BRI Syariah facing problems in financing less current than Syariah BRI customers.